Implementasi Golang dan New Simple Queue pada Sistem Sandbox Pihak Ketiga Berbasis REST API - Albertus Ari Kristanto; Yulius Harjoseputro; Joseph Eric Samodra (Ikatan Ahli Informatika Indonesia (IAII), 2020)
A good application development requires a testing phase to ensure there are no errors before it’s released to public. But testing phase becomes difficult if the application development involves features from third parties. The idea to resolve the problem for Dhanapala application under the auspices of PT. Semangat Gotong Royong is to make the Sandbox system which is a system designed to resemble the characteristics of a third party. The Sandbox system will be developed into a REST API and written using the Golang programming language. In conducting communications with other systems New Simple Queue (NSQ) is also used that can support concurrency and prevent data transmission failures. As a result, the Sandbox system can receive requests and will process responses that are similar to functions from third parties. All forms of feature calls to third parties can be transferred to the Sandbox system so that all the data needs on some functions involving third parties can be fulfilled and the Dhanapala application can be run without its dependence on third parties